Aplikasi Teknologi Berbasis Android Untuk Mempermudah Penyajian Informasi Golongan Darah Yang Cepat Dan Tepat Bagi Masyarakat Desa - Octavia, Mega; Kurniawan, Yuda Fatah (Universitas Muhammadiyah Yogyakarta, 2018)
The community’s contribution in blood donation is the main factor to determine the availability and assistance of health facilities. Based on data from the public health department, the percentage of mortality especially for pregnant women is caused by bleeding is 28%. This isssue can be dealt through the activiness of community citizens as donors. Currently, there are several problems to fulfill the needs of blood services in terms of both quantity and time. This activity is conducted with the aim to facilitate the presentation of blood types information quickly and accurately for the community. The method applied in the activity begins with the socializing to ccommunity with the benefits of blood, data collection of blood type from community, blood type test, data input, android application, and socialization the using of android applications to the residents. Application of android technology can be used for data input , data presentation and search for the necessary datakeyword : Public health information, based android, blood type